Effectiveness of Supervision Programs on Improving Teaching Skills and Teacher Performance in Schools - Iman Abdul Sobar (Journal of Educational Management Research, 2025)
This study evaluates the effectiveness of supervision programs in enhancing teaching skills, teacher performance, and learning quality at SD Negeri 013 Tana Tidung. A quantitative survey method was employed, involving 19 teachers as the main population and 24 students from grades 4 to 6 as additional participants. Data was collected using questionnaires and structured interviews, with analysis performed through descriptive and correlational statistics. The findings indicated that the supervision program led to significant improvements in all three variables: teaching skills increased by 28% (from 3.2 to 4.1 on a 5-point scale), teacher performance improved by 22% (from 72 to 88 on a 100-point scale), and students' average scores rose by 15% (from 68 to 78 on a 100-point scale). Supervision methods such as teacher meetings, teaching demonstrations, and classroom observations effectively provided constructive feedback to enhance teaching practices. However, the study faced limitations, including a small sample size and reliance on teachers' perceptions for data collection. Future research should expand the sample size and incorporate diverse methods, like direct observation and longitudinal analysis, to assess student outcomes. These findings offer valuable insights into improving educational supervision in primary schools.